Building a More Resilient Haitian State - Crane, Keith (RAND Corporation, 2010)
Hope for a prosperous and peaceful future for Haiti lies in building a more effective, resilient state. This report identifies the main challenges to more capable governance, evaluates existing plans for improving the delivery of public services, and proposes a realistic set of critical actions. The proposed state-building priorities merit the greatest degree of Haiti's andinternational donors' policy attention and financial commitment.